Are Names Really Empty: A Look into Shona Dog Names - Isaac Mhute (European Scientific Journal, ESJ, 2016)
Following the popular Shakespearean saying that there is nothing in a name, the paper ventures into the linguistic area of onomastics focusing on uncovering the exact truth behind names in societies. It takes the Shona people’s dog names as a case study and reports on results from a qualitative research that used observations and open ended interviews as data collection techniques. Purposive sampling was employed and saw most of the data coming from districts in Masvingo province such as Zaka, Masvingo and Ndanga. Data were either recorded using a Samsung phone or recorded in the researcher’s notebook before being qualitatively analysed and interpreted. It came out that, though in certain situations names are just tags meant to enhance identification of certain dogs just like the Biblical names that were given to most African children following the coming of the former white masters, almost every Shona dog name has a story behind it.